Antioxidant and anticancer activity of Canarium ovatum Engl. (Pili) ethanolic leaf extracts - Terrazola, Rafael Joseph Itao; Manzanares, Djamae Librado; Morilla, Lady Jane Gacasan; Anunciado, Loren Grace Jaranilla; Olowa, Lilybeth Flores; Amparado, Olive Anies (Intelektual Pustaka Media Utama, 2025)
The Pili (Canarium ovatum Engl.) tree, native to the Philippines, has been reported to have medicinal properties because of the biological and chemical properties it exhibits. This paper aimed to investigate the presence of phytochemicals, antioxidant, and anticancer activities of the ethanolic leaf extract of C. ovatum. To determine the phytochemicals, present in the extract, standard procedures for qualitative phytochemical screening were performed. The antioxidant activity of the extract was assessed in vitro using 2,2-Diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging assay. The anticancer activity of the extract was assessed in vitro using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) cell viability assay against the HCT116 cancer cell line. Phytochemical screening of C. ovatum ethanolic leaf extract detected alkaloids, steroids, flavonoids, saponins, and tannins. The extract had extremely high antioxidant activity (IC50=11.44 mg/L). The MTT assay revealed moderate cytotoxic activity of the leaf extract to HCT116 cancer cell line (IC50=94.43 mg/L). These findings suggest that the C. ovatum ethanolic leaf extract has therapeutic potential because of the presence of beneficial phytochemicals, strong antioxidant activity, and anticancer capacity. Futher research is recommended to comprehensively evaluate the medicinal potential of Pili leaf extracts, including exploring other biological activities using various assays and employing different solvents for leaf extraction.